2011
DOI: 10.1007/s12105-011-0298-3
|View full text |Cite
|
Sign up to set email alerts
|

Glandular Odontogenic Cyst: Analysis of 46 Cases with Special Emphasis on Microscopic Criteria for Diagnosis

Abstract: The glandular odontogenic cyst (GOC) is now a relatively well-known entity with recent reviews indicating over 100 cases reported in the English literature. The GOC's importance relates to the fact that it exhibits a propensity for recurrence similar to the odontogenic keratocyst, and that it may be confused microscopically with central mucoepidermoid carcinoma (CMEC). Numerous histopathologic features for the GOC have been described, but the exact microscopic criteria necessary for diagnosis have not been uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
172
1
21

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(240 citation statements)
references
References 41 publications
4
172
1
21
Order By: Relevance
“…Glandular odontogenic cyst (GOC) is an uncommon benign cystic lesion of the gnathic bones initially described in 1987 as ''sialo-odontogenic cyst'' or ''mucoepidermoid odontogenic cyst.'' [6][7][8][9][10][11][12][13][14][15][16] Since its first description, many investigators have recognized that GOC shares many histologic features with central MEC [1,2,5,7,9,10,[16][17][18][19][20]. Indeed, it is common to see areas indistinguishable from GOC within a central MEC [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glandular odontogenic cyst (GOC) is an uncommon benign cystic lesion of the gnathic bones initially described in 1987 as ''sialo-odontogenic cyst'' or ''mucoepidermoid odontogenic cyst.'' [6][7][8][9][10][11][12][13][14][15][16] Since its first description, many investigators have recognized that GOC shares many histologic features with central MEC [1,2,5,7,9,10,[16][17][18][19][20]. Indeed, it is common to see areas indistinguishable from GOC within a central MEC [2].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is common to see areas indistinguishable from GOC within a central MEC [2]. Conversely, ''MEC-like'' areas within the walls of GOCs have been described [10].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of epithelial sphere or whorl can be observed in a wide variety of odontogenic cysts including lateral periodontal, botryoid, glandular, adult gingival as well as dentigerous cysts [31]. Alternatively, histologically similar morular structures have been reported in the cribriform-morular variant of papillary thyroid carcinoma (CMVPTC) [32].…”
Section: Discussionmentioning
confidence: 98%
“…GOC has been traditionally described as predominantly affecting middle-aged individuals in their 4th-7th decades of life (mean=45.9 years-old) (2,3). While some studies report no significant gender predilection (1,3,(6)(7)(8), others have reported a slight male predominance of 1.3:1 to 2:1 (2,9,10). GOC commonly affects the mandible 2-3x as often as it does the maxilla (1,2,7,8,10).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies report no significant gender predilection (1,3,(6)(7)(8), others have reported a slight male predominance of 1.3:1 to 2:1 (2,9,10). GOC commonly affects the mandible 2-3x as often as it does the maxilla (1,2,7,8,10). Some reports claim a preference for the anterior mandible (3,6,8), but others indicate equal distribution between anterior and posterior mandibular segments (2).…”
Section: Introductionmentioning
confidence: 99%